The Relationship between Cost of Treatment and Cognitive Deficit in Schizophrenia - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Schizophrenia is not only a complex and disabling illness, but also costly. Cognitive impairment is a major determinant of functional outcome of patients.Aims:To determine the relationship between the direct cost of treatment and the cognitive impairment in schizophrenia.Settings and Design:This is a longitudinal study at a tertiary mental health facility in northern Nigeria.Materials and Methods:This study involved 270 patients with schizophrenia aged 15–64 years. Instruments used included Schizophrenia Cognition Rating Scale (SCoRS), the Mini International Neuropsychiatric Interview PLUS and a modified cost of illness (COI) questionnaire.Statistical analysis used:All tests of statistics were carried out at 5% level of probability.Results:A total of 270 participated in this study with a male: female ratio of almost 1. The mean age of participants 33.04 years. Majority were unemployed (51.5%), single (45.6%) and of low socioeconomic class (88.5%). Lower SCoRS for stable patients was significantly associated with higher educational attainment, occupational and marital status, high socioeconomic status and absence of caregiver. SCoRS had a significant correlation with duration of untreated psychosis, COI, age at onset, duration of illness, length of caregiving and number of caregivers.Conclusion:Cognitive impairment experienced by patients with schizophrenia are numerous, not only by the suffering and limitations it imposes on them, but also the enormous cost and burden that comes with caregiving. Efforts geared toward early detection and presentation of schizophrenia patients, and subsidizing cost of drug by government will go a long way in reducing cognitive impairment among patients.